2020
DOI: 10.18203/2349-3291.ijcp20201148
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to exclusive breast feeding, the missing links: a cross sectional study from Puducherry, India

Abstract: Background: Breast milk, the first natural food for a new-born, provides all the energy and essential nutrients an infant requires for the first 6 months of life. The NHFS -4 survey shows only 45.5% of children are exclusively breastfed (EBF) in Puducherry. This study aims at assessing the socio-demographic characteristics associated with exclusive breastfeeding in a tertiary hospital in Puducherry and identify the barriers in the promotion of exclusive breastfeeding.Methods: Community-based cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Several studies showed that pre-lacteal feeding rituals were major barriers to exclusive breastfeeding. The practice of giving newborn babies pre-lacteal feeds like jaggery, honey, sugar water, cow milk, and ghee was observed by many previous studies [ 27 , 47 , 49 – 51 , 54 ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies showed that pre-lacteal feeding rituals were major barriers to exclusive breastfeeding. The practice of giving newborn babies pre-lacteal feeds like jaggery, honey, sugar water, cow milk, and ghee was observed by many previous studies [ 27 , 47 , 49 – 51 , 54 ].…”
Section: Resultsmentioning
confidence: 98%
“…Lack of counselling on proper breastfeeding practice and their benefits were major barriers to delay in breastfeeding initiation or exclusive breastfeeding [ 20 , 21 , 49 , 53 ]. Additionally, it was observed that mothers who devoted their maximum time to domestic chores did not have time to adhere to early breastfeeding [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, lack of counselling on proper breastfeeding practice and its bene ts were major barriers towards delay in breastfeeding initiation or exclusive breastfeeding [20,21,43,52]. Additionally, due to increased domestic workload, mothers did not have proper time to adhere to early breastfeeding [24].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Note: N.A: Not available; NFHS: National Family Health Survey; DLHS: District Level Health Survey; CNSG: Comprehensive Nutrition Survey in Gujarat; FGD: Focus group discussion; IDI: In-depth interviewIndividual and interpersonal barriersA total of 30 studies, including seventeen quantitative[2,4,5,9,11,18,21,22,24,[28][29][30]40,[43][44][45][46], ten qualitative[1,8,23,26,35,50,52,53,57,58] and three mix-method studies…”
mentioning
confidence: 99%